Emission Prediction of Municipal Solid Waste by Physical and Chemical Characteristics Analysis - Chung, Jin-Do; Kim, Jin-Wan; Hwang, Seung-Min (Asian Journal of Chemistry, 2013)
In this study, we investigated medium long-term physico-chemical characteristics of domestic waste in small and medium cities of Chungcheongnam-do, C city, A city and D gun. Apparent density, physical composition, three ingredients, elementary composition and caloric value of domestic waste of each area in winter season were analyzed in accordance with the waste process test method. The basic unit emission of domestic waste was calculated and future production was predicted. The result of analysis indicates that no difference in apparent density was shown by district and, as to physical composition, food in C city and A city and paper in D gun showed the highest percentages. The result of analyzing elementary composition showed that carbon content and oxygen content in D gun were lower than those of C city and A city. Also, in the analysis of caloric values, D gun was the lowest showing a value of 2188 kcal/kg in comparison to those of C city and A city which were 2,634 kcal/kg and 2,231 kcal/kg, respectively. As to the basic unit emission, while there was no big difference between C city and A city which were 1.11 kg/day·person and 1.02 kg/day·person respectively, D gun was 0.63 kg/day·person showing a big difference.